PENGEMBANGAN MEDIA FLASH MATERI IKATAN KIMIA SISWA KELAS X SMA NEGERI 1 PONTIANAK - Ananda Rizki Shelawaty; Dini Hadiarti; Raudhatul Fadhilah (Jurnal Ilmiah Ar-Razi, 2016)
ABSTRACTThis study aimed by the students’ low mastery score on Chemical Bond material at SMA Negeri 1 Pontianak. The mastery score gained by the students was only 44,3%. Based on the results of the questionnaires given to the students, they tend to study by using computer than power point program and video that have been used by the teachers. Therefore, this study aimed to develop teaching materials of Chemical Bond flash media for the students of grade X, SMA Negeri 1 Pontianak. A 3D (Define, Design, and Develop) development model suggested by Thiagarajan was carried out in this study. The data collection technique used were indirect communication, measurement, and observation. While the instruments were questionnaire sheets, pre-test and posttest questions, and observation sheet. The feasibility of the flash media developed was based on the aspects of validity, practicality, and effectiveness. The results obtained in this study were: (1) the average score of the flash media validity was 89.78% and was considered valid, (2) the practicality of the media based on the students’ response was 80.02% and was considered very strong and the teacher’s response was 75% and considered strong, and (3) the effectiveness of the media based on the learning outcomes showed significant results between before and after using the media (0.000 <0.05). As a result, flash media is regarded successful developed for the students of SMA Negeri 1 Pontianak and it is applicable to teach Chemical Bond material. Keywords: Chemical Bond, Flash media, media development